Genetic correlation and path analysis for the number of commercial fruit per plant in papaya - Oliveira, Eder Jorge; Lima, Diego Souza de; Lucena, Rangel Sales; Motta, Tiago Borges Nunes; Dantas, Jorge Luiz Loyola (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to determine how the number of commercial fruit per plant (CFrP) is related to 16 morphological and agronomical traits in papaya (Carica papaya L.). The experiment was carried out in the 2008/2009-crop season, using an augmented randomized block design. Nineteen non-common (germplasm accessions) and three common genotypes (varieties and hybrids) were evaluated with ten repetitions. Correlations between CFrP and morpho-agronomic traits were outspread in direct and indirect effects. High variability was found for the evaluated traits. The estimates of genetic correlations were higher than phenotypic correlations for all characters. CFrP was positively and significantly correlated with number of fruits per axil (NFAx) and negatively with the internal diameter of the cavity of the fruit, pulp thickness, fruit weight, fruit length (FrL) and fruit diameter. However, path analysis showed that, among this traits, NFAx and FrL have more direct effect on CFrP. Furthermore, plant height, number of flowers per peduncle and leaf width are more easily measured and are expressed before fruit production, making them more suitable for indirect selection in breeding programs of this crop.